Re-framing women"s agency in #Blessed sex: Intersectional dilemmas for African women"s theologies - Haddad, Beverley (HTS teologiese studies, 2021)
The Circle of Concerned African Women Theologians has since its inception, affirmed the agency of women in their theological reflection and praxis. In doing so, they have called on their male colleagues to stand in solidarity with them in forging alternative masculinities that renew culture, curb gender-based violence and mitigate HIV infection. This essay argues that there are three assumptions that form the basis of the work of the Circle theologians. Firstly, that women seek to be in egalitarian relationships with men that bring dignity and respect. Secondly, women assert their agency to achieve this goal and in so doing bring healing and wholeness to both groups who are transformed through this process. Thirdly, women assert their agency in solidarity with other women as they build alternative egalitarian communities. Yet, the recent phenomenon of the #Blessed community of young women who seek out ‘blessers’, older men who engage them in transactional sex, in order to fund opulent lifestyles contradicts these assumptions. Their agency embraces non-liberative ideology and practice and chooses not to unseat the dominant ideologies of hetero- and econo-patriarchy.Contribution: The essay concludes that a lack of sustained economic analysis and engaged theological reflection on sexual ethics means the Circle is ill-equipped to respond to the challenge posed by the #Blessed community of young women.